2020
DOI: 10.1186/s41235-020-00239-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial activity participation in childhood and adolescence: consistency and relations to spatial thinking in adolescence

Abstract: Background Prior research has revealed positive effects of spatial activity participation (e.g., playing with blocks, sports) on current and future spatial skills. However, research has not examined the degree to which spatial activity participation remains stable over time, and little is known about how participating in spatial activities at multiple points in development impacts spatial thinking. In this study, adolescents completed measures of spatial thinking and questionnaires assessing their current and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Research has shown, for example, that performance on spatial tests such as mental rotation is correlated with the experience of playing video games (Feng, Spence, & Pratt, 2007 ; but see Redick, Unsworth, Kane, & Hambrick, 2017 ; Unsworth et al., 2015 ). And students' performance in academic learning is discussed in relation to past experience of participating in spatial activities (Peterson, Weinberger, Uttal, Kolvoord, & Green, 2020 ). In the context of cognitive mapping, a greater amount of experience of spatial activities correlates with better wayfinding performance and the tendency to use orientation strategies in navigation, as well as higher mental rotation scores (Lawton & Kallai, 2002 ; Moè, Jansen, & Pietsch, 2018 ; Vieites et al., 2020 ).…”
Section: Why Good and Poor Navigators?mentioning
confidence: 99%
“…Research has shown, for example, that performance on spatial tests such as mental rotation is correlated with the experience of playing video games (Feng, Spence, & Pratt, 2007 ; but see Redick, Unsworth, Kane, & Hambrick, 2017 ; Unsworth et al., 2015 ). And students' performance in academic learning is discussed in relation to past experience of participating in spatial activities (Peterson, Weinberger, Uttal, Kolvoord, & Green, 2020 ). In the context of cognitive mapping, a greater amount of experience of spatial activities correlates with better wayfinding performance and the tendency to use orientation strategies in navigation, as well as higher mental rotation scores (Lawton & Kallai, 2002 ; Moè, Jansen, & Pietsch, 2018 ; Vieites et al., 2020 ).…”
Section: Why Good and Poor Navigators?mentioning
confidence: 99%
“…Studies have shown that engaging in spatial activities (e.g., puzzles and block building) positively influences spatial thinking and reasoning (Baenninger & Newcombe, 1989, 1995; Casey et al., 2008; Cherney, 2008; Costa‐Giomi, 1999; Doyle et al., 2012; Jirout & Newcombe, 2015; Levine et al., 2012; Ozel et al., 2004; Weckbacher & Okamoto, 2012). Further longitudinal work showed that participation in spatial activities in childhood predicted spatially related problem‐solving strategies and spatial ability as well as participation in spatial activities in adolescence (Peterson et al., 2020). Even a small amount of training (e.g., formal curriculum, spatial video games, etc.)…”
Section: Theoretical Perspectives On Spatial Cognitionmentioning
confidence: 99%
“…Finally, there are still parts of the system that are important driving factors not currently being considered, such as lived experiences (Coutrot et al, 2022;Harris et al, 2022), the tendency to apply spatial thinking, regardless of skill level (Kim and Bednarz, 2013;Peterson et al, 2020), and the tools and representations indicative of spatial thinking but not measured by current tests (Newcombe, 2018;Logan et al, 2022). These factors are influential and should be incorporated to support student learning (National Research Council, 2006).…”
Section: Taking a Broader View Of Spatial Researchmentioning
confidence: 99%